Ventricular orexin-A (hypocretin-1) levels correlate with rapid-eye-movement sleep without atonia in Parkinson's disease - Bridoux A (Dove Medical Press, 2013)
Agathe Bridoux,1,2 Stephane Moutereau,3 Ala Covali-Noroc,1 Laurent Margarit,1 Stephane Palfi,4 Jean-Paul Nguyen,5 Jean-Pascal Lefaucheur,1,2 Pierre Césaro,6 Marie-Pia d'Ortho,7 Xavier Drouot1,21Service de Physiologie, Groupe Henri Mondor, 2Faculté de Médecine, Université Paris Est Créteil, 3Service de Biochimie, Groupe Henri Mondor, 4UF Neurochirurgie Fonctionnelle, Groupe Henri Mondor, Créteil, France; 5Service de Neurochirurgie, Hôpital Nord Laënnec, Nantes, France; 6Service de Neurologie, Groupe Henri Mondor, Créteil, France; 7Service de Physiologie, Groupe Bichat – Claude Bernard, Paris, FranceObjective: Patients with Parkinson's disease frequently complain of sleep disturbances and loss of muscle atonia during rapid-eye-movement (REM) sleep is not rare. The orexin-A (hypocretin-1) hypothalamic system plays a central role in controlling REM sleep. Loss of orexin neurons results in narcolepsy-cataplexy, a condition characterized by diurnal sleepiness and REM sleep without atonia. Alterations in the orexin-A system have been also documented in Parkinson's disease, but whether these alterations have clinical consequences remains unknown.Methods: Here, we measured orexin-A levels in ventricular cerebrospinal fluid from eight patients with Parkinson's disease (four males and four females) who underwent ventriculography during deep brain-stimulation surgery and performed full-night polysomnography before surgery.Results: Our results showed a positive correlation between orexin-A levels and REM sleep without muscle atonia.Conclusion: Our results suggest that high levels of orexin-A in Parkinson's disease may be associated with loss of REM muscle atonia.Keywords: Parkinson, orexin-A, ventricular CSF, REM atonia